Impact of Trade Liberalization on Economic Growth in Small Developing Economies: Bhutan as a Case Study - Khandu, Pema (Asian Journal of Empirical Research, 2014)
This paper examined the relationship between trade liberalization and economic growth in the context of Bhutan’s fragile economy. The study used a cross-country growth regression analysis under a fixed-effects model using dynamic panel data. A sample of 20 homogenous countries from different regions was used in the analysis. The countries were selected based on the following criteria: land size, population, economy, geography, and resource dependence. Given the complexity of constructing a trade openness index in the absence of adequate data, the study used the ratio of total trade (exports + imports) to real GDP as a proxy for trade liberalization. Accordingly, a country with a higher trade openness index was considered more liberal and outward-oriented in terms of international trade than a country with a lower openness index. Regression results show that trade liberalization has a positive and significant effect on growth, which is consistent with much of the earlier theoretical and empirical literature in the field. This suggests that efforts to pursue outward-oriented trade policy regimes may be beneficial for long-term economic growth in Bhutan and other similar economies.